Which Emerging Markets and Developing Economies Face Corporate Balance Sheet Vulnerabilities? : A Novel Monitoring Framework - Feyen, Erik; Fiess, Norbert; Zuccardi Huertas, Igor; Lambert, Lara (World Bank, Washington, DC, 2017)
This paper introduces a novel corporate financial vulnerability index that tracks financial conditions of the non-financial corporate sector. Using the balance sheet information of 14,207 listed non-financial firms in 69 emerging markets and developing economies, the index shows that, at the global level, corporate vulnerability sharply increased since 2013 and stabilized in 2016. Regional trends are more heterogeneous, pointing to significant corporate vulnerabilities in Eastern Europe and Central Asia, as well as a deterioration of firms' financial conditions in Latin America, the Middle East and North Africa, and Sub-Saharan Africa in recent years. The energy sector has exhibited the fastest deterioration, especially since 2014, in part driven by the decline in oil prices. However, if currently relatively benign global funding conditions and higher commodity prices endure, companies may have an opportunity to strengthen their balance sheets. The paper also finds that the index has leading indicator properties for socioeconomic outcomes, such as a rise in unemployment and an economic recession, and outperforms a commonly used "debt at risk" approach.